Hunza indigenous settlement prior to the conquest. An overview from the imaginaries - Portilla Tarazona, Jairo Arturo (Universidad Pedagógica y Tecnológica de Colombia, 2021)
The aim of this investigation was to establish how the Hunza indigenous community maintained their ceremonial and symbolic centres in the 16th century, when the Spanish arrived, as a natural and cultural process that was part of their imaginaries and collective identities. With respect to this, a geographic study of the Hunza settlement was carried out, according to the physical characteristics of the landscape and the terrain, as well as the relationships between the geographical space and the imaginaries created by their inhabitants, which are an expression of their cosmogony.